Model of Institutional Capacity Development in Building Balbar into an Independent Village in Tidore Municipality - Isra Muksin; Karim Merua (Yayasan Ilomata, 2026)
Balbar Village is the only independent village in Tidore City, North Maluku Province because it is supported by human resource development, organizational development, and institutional reform. The purpose of this research is to get an overview of institutional capacity development in building an independent village and the implementation of programs every year to get a complete picture of human resource development, organizational development and institutional reform in Balbar Village. This research uses a qualitative method approach that delves deeper into the phenomenon and examines the substance of the meaning behind the phenomenon of village institutional capacity development. Deepening qualitative research on the process and interpretation of the results. In qualitative research, human beings are the main focal point, as well as interaction between institutions in an effort to understand an event. The results of the study found that human resource development has been optimal, and Improvement of Technical and Managerial Competencies has been implemented well. Meanwhile, in terms of organizational development, it is not optimal for other institutions to be improved, and institutional reforms have not been fully implemented in Balbar Village, especially accountability has not yet used digital information systems. Meanwhile, institutional reform has not been optimally implemented because village autonomy has not been fully given to the widest extent. It is recommended that in building village independence, optimize organizational development and institutional reform. His next follow-up research is related to governance innovation in building independent villages.